Analysis of Contaminant Load Capacity of Nitrate and Phosphate in Krukut River - Muhammad Akmal Muliawan; Riana Ayu Kusumadewi; Melati Ferianita Fachrul (Journal of Community Based Environmental Engineering and Management, 2022)
The Krukut River is one of the major rivers that flow in the Jakarta area and has an essential role in supporting public activities in the city. It is designated as raw water for drinking water. The study was conducted in the 44.30 km Krukut River flow from September 2021 until February 2022. The purpose of this study was to analyze the pollutant load capacity of nitrate and phosphate. Parameters measured in this study were temperature, turbidity, DHL, pH, DO, nitrate and phosphate. Identification of pollutant sources was carried out by field surveys. Water quality analysis is carried out following SNI (Indonesian Standard) and compared with quality standards according to Government Regulation no. 22 of 2021, as well as analysis of the pollutant load capacity of nitrate and phosphate. The search results for potential pollutants in the Krukut River are dominated by domestic waste. The air quality analysis simulation results show that the phosphate curve tends to increase with increasing distance, while the nitrate concentration fluctuates. The results of water quality analysis for nitrate parameters ranged from 1.52 mg/L – 2.94 mg/L, and phosphate ranged from 0.21 mg/L – 1.37 mg/L. The pollutant load carrying capacity results a (PLCC) average for nitrate parameters is 2431.94 kg/day, and phosphate is 48.64 kg/day, with an average pollutant load for nitrate parameters 579.84 kg/day, phosphate 243.02 kg/day.